2013
DOI: 10.1093/jxb/ert072
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of TaSnRK2.3, a novel SnRK2 gene in common wheat

Abstract: Environmental stresses such as drought, salinity, and cold are major adverse factors that significantly affect agricultural productivity. Protein phosphorylation/dephosphorylation is a major signalling event induced by osmotic stress in higher plants. Sucrose non-fermenting 1-related protein kinase 2 (SnRK2) family members play essential roles in the response to hyperosmotic stresses in plants. In this study, the TaSnRK2.3 gene, a novel SnRK2 member was cloned, and three copies located on chromosomes 1A, 1B, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 67 publications
(87 reference statements)
10
62
0
Order By: Relevance
“…The PYR/PYL/RCAR family of proteins are ABA receptors that can inhibit the activity of the type-2C protein phosphatase PP2C in the presence of ABA, relieving the repression of the SnRK2 kinases activity, which in turn phosphorylates other downstream regulators (Furihata et al 2006;Ma et al 2009;Park et al 2009). Overexpression of TaSnRK2.3 in Arabidopsis results in enhanced root-system architecture and significantly enhances the tolerance of this species to drought, salt, and freezing stresses (Tian et al 2013), whereas downregulation of PP2CA proteins increases ABA sensitivity and accelerates cold acclimation in transgenic plants (Tahtiharju and Palva 2001). Promoter analysis found that some DRE/CRT motif-containing COR genes are induced by cold and dehydration and impaired in ABA-deficient mutants (Thomashow 1999;Shinozaki and YamaguchiShinozaki 2000).…”
Section: The Role Of Aba Biosynthesis and Signalling In Cold Stressmentioning
confidence: 99%
“…The PYR/PYL/RCAR family of proteins are ABA receptors that can inhibit the activity of the type-2C protein phosphatase PP2C in the presence of ABA, relieving the repression of the SnRK2 kinases activity, which in turn phosphorylates other downstream regulators (Furihata et al 2006;Ma et al 2009;Park et al 2009). Overexpression of TaSnRK2.3 in Arabidopsis results in enhanced root-system architecture and significantly enhances the tolerance of this species to drought, salt, and freezing stresses (Tian et al 2013), whereas downregulation of PP2CA proteins increases ABA sensitivity and accelerates cold acclimation in transgenic plants (Tahtiharju and Palva 2001). Promoter analysis found that some DRE/CRT motif-containing COR genes are induced by cold and dehydration and impaired in ABA-deficient mutants (Thomashow 1999;Shinozaki and YamaguchiShinozaki 2000).…”
Section: The Role Of Aba Biosynthesis and Signalling In Cold Stressmentioning
confidence: 99%
“…Environmental stresses often cause physiological changes in plants, so such indices are used to evaluate abiotic stress tolerance and resistance in crops (Tian et al 2013). ROS is the main product of heat stress, and MAPKs are the key players in ROS signaling (Pitzschke and Hirt 2009;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Total chlorophyll content was measured with a chlorophyll meter (SPAD 502 Plus; Konica Minolta Sensing) as described previously (Abe et al 2012;Tian et al 2013). Measurements of chlorophyll content under stress conditions were performed after applying a treatment of 37 °C for 3 days.…”
Section: Chlorophyll Measurementmentioning
confidence: 99%
“…Recently, the AtSnRK2.6 protein was found to mediate the regulation of sucrose metabolism and plant growth in Arabidopsis (Zheng et al 2010). In our previous study, the overexpression of wheat SnRK2s in Arabidopsis resulted in high total soluble sugars and enhanced tolerance to stresses Zhang et al 2011c;Tian et al 2013) It was speculated that soluble sugar accumulation may lower the osmotic potential in the plant sap, maintaining regular cell turgor and avoiding damage to cell membranes that would enhance osmotic stress. In the present study, TaSnRK2.7 transcripts and total soluble sugars increased significantly under PEG treatments (figure 3), indicating that TaSnRK2.7 and sugar metabolism is playing a role in stress tolerance.…”
Section: Expression Patterns Of Tasnrk27 In Wheat Speciesmentioning
confidence: 99%
“…Individual members of SnRK2 have acquired different regulatory properties under stress signaling (Boudsocq et al 2007;Huai et al 2008;Mao et al 2010;Tian et al 2013;Xu et al 2013). Furthermore, SnRK2 kinases are also involved in the regulation of carbon metabolism and energy status in their respective systems, similar to the function of sucrose nonfermenting 1 (SNF1) in yeast, which is activated in response to low cellular glucose levels by directly modulating the * For correspondence.…”
Section: Introductionmentioning
confidence: 99%